Perception of Leader-member Exchange: Evidence from Employees in a Nonprofit Organization - Putsom, Wanlee; Fangpet, Pratoomma; Hamra, Wayne (11th International Scholars Conference, 2017)
The purposes of this survey research were to 1) investigate the perception of leader-member exchanges (LMX) among employees, and 2) compare differences in perception by gender, education level, age, marital status, work experiences, and job position among these respondents. The sample was 113 employees who worked in a nonprofit organization. The findings showed that most employees agreed that “My working relationship with my supervisor is effective” (4.07). Support for statement that “My supervisor and I are suited to each other” was slight lower, with an average score of 3.89. No significant differences in perception were found based upon gender, age, marital status, and work experience, but there was a significant difference at the 0.05 level based upon employees’ educational backgrounds and job positions. This study provides insight into the views of LMX from the perspective of a nonprofit organization’s employees, along with implications, contributions, limitations, and suggestions for future research.